Lexical cross-linguistic influence: a study of three multilingual learners of L3 English. Issue 4 (1st October 2020) - Efeoglu, Gulumser; Yüksel, H. Gülru; Baran, Suat
ABSTRACT: In a world where multilinguals outnumbered monolinguals, the study of the third language (L3) acquisition has been an area of interest for many researchers. This case study investigates the lexical cross-linguistic influence of previously acquired languages on the subsequent acquisition of English as L3 by Pomak multilingual speakers residing in Xanthi, Greece. For the purpose of this study, three different participants' texts written in English were collected. The non-target productions identified in the texts were tagged and analysed. In line with the Parasitic Model of L3 Vocabulary Acquisition [Hall, C. J., & Ecke, P. (2003). Parasitism as a default mechanism in L3 vocabulary acquisition. In J. Cenoz, B. Hufesien, & U. Jessner (Eds.), The multilingual lexicon (pp. 71–85). Dordrecht: Springer] results indicate that the participants resort to different languages for different linguistic categories in their L3 written production. They also suggest that such lexical CLI may be due to English proficiency rather than the order of acquisition and language use.